Delayed start-up of kinesin-driven microtubule gliding following inhibition by adenosine 5'-[beta,gamma-imido]triphosphate. - Schnapp, B J (1990)
Kinesin is a microtubule-activated ATPase that moves objects toward the plus end of microtubules and makes microtubules glide along a glass surface. Here we investigate a remarkable effect of the nonhydrolyzable analogue of ATP, adenosine 5'-[beta,gamma-imido]triphosphate (p[NH]ppA), on kinesin-driven microtubule gliding. Microtubule gliding that has been blocked by rapid replacement of ATP with p[NH]ppA requires 1-2 min of exposure to ATP before microtubule gliding resumes. This latency is not shortened by prolonged washing of p[NH]ppA-blocked microtubules in nucleotide-free buffer for up to 15 min, suggesting that ATP binding to a second nucleotide binding site on kinesin triggers the release of bound p[NH]ppA. To test this hypothesis, the release of [3H]p[NH]ppA from kinesin-microtubule complexes was followed in parallel biochemical assays. In nucleotide-free buffer, the bound p[NH]ppA was released over several hours from the complexes. However, addition of ATP caused the release of p[NH]ppA from the kinesin-microtubule complexes within 2 min, which was similar to the latent period for start-up of microtubule gliding after p[NH]ppA inhibition. The stoichiometry of p[NH]ppA bound per kinesin heavy chain at saturation was estimated to be approximately 1:2. These results suggest a model in which each molecule of kinesin has at least two nucleotide binding sites that alternately bind nucleotide.